Data Fusion in Wireless Sensor Network: An Overview - Kaschel-Carcamo, H; Kern-Molina, J (Institute of Electrical and Electronics Engineers Inc., 2023)
Due to the massive increase in data sets in contemporary applications and the difficulty of their processing in various approaches, data fusion remains a predominant way to obtain outstanding results, in terms of reliability, efficiency, and precision. The following document presents an overview of data fusion in wireless sensor networks; in which, various concepts to applications are considered to generate a base document for future research. This article gives a comprehensive and current view of models or architectures, techniques, methodologies or algorithms, and a current review of applications in different areas. © 2023 IEEE.